The stem of Schisandra chinensis and Schisandrin B alleviated DNCB-induced atopic dermatitis in mice by inhibiting the NF-κB pathway - Ye, Cai; Liu, Yijie; Li, Yue; Li, Zan; Sui, Liyuan; Cui, Jiwen; Jiang, Zihao; Li, Jinlian; Song, Jianjun; Liu, Jiguang (Frontiers in Immunology, 2026)
BackgroundAtopic dermatitis (AD) is a chronic, pruritic, inflammatory skin disorder. While the stem of Schisandra chinensis has been extensively studied for its pharmacological properties, including anti-inflammatory, antioxidant, and hepatoprotective effects, its therapeutic potential in AD remains to be elucidated. This study therefore aimed to investigate the effects of Schisandra chinensis stem extract (SCSE) against AD and to explore its underlying mechanism of action.MethodsChemical profiling of SCSE via UPLC-Q-Exactive-Orbitrap-MS revealed 45 constituents, with lignans comprising 80%. The primary active component was identified through activity-guided assays employing hyaluronidase inhibition and HPLC. The therapeutic efficacy of SCSE and its constituent Schisandrin B (Sch B) was assessed in an AD mouse model. Furthermore, network pharmacology predicted the involved signaling pathways, and these predictions were subsequently validated experimentally.ResultsSch B was identified as the core active component. Both SCSE and Sch B significantly improved skin barrier function in AD mice, as evidenced by reduced transepidermal water loss (TEWL) and upregulation of key barrier proteins (Filaggrin, Loricrin, and Claudin-1). They also alleviated pruritus by suppressing Transient Receptor Potential Vanilloid 1 (TRPV1) and mitigated the allergic-inflammatory response, as shown by reduced Immunoglobulin E (IgE) levels and inhibited release of mast cell (MC) mediators (IL-4, IL-6, TNF-α). These effects were potentially mediated through modulation of the NF-κB pathway.ConclusionBy simultaneously mitigating skin barrier dysfunction, immune inflammation, and pruritus, SCSE and Sch B hold promise as therapeutic candidates capable of disrupting the self-perpetuating cycle of AD. These findings position SCSE and Sch B as a novel therapeutic strategy for this disease.